Predictive value of the fibrinogen-to-albumin ratio for hemorrhagic transformation following intravenous thrombolysis in ischemic stroke: a retrospective propensity score-matched analysis - Liu, Xiao-Yu; Jia, Hui-Yang; Wang, Gang (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to explore the factors associated with hemorrhagic transformation (HT) in acute ischemic stroke patients after intravenous thrombolysis (IVT), with a specific focus on the relationship with the post-thrombolysis fibrinogen-to-albumin ratio (FAR).MethodsThe clinical records of 569 acute ischemic stroke (AIS) patients admitted to our department from 2020 to 2023 were retrospectively analyzed. All eligible patients were stratified into HT and non-HT (NHT) groups. Propensity score matching (PSM) was performed between the two groups. Receiver operating characteristic (ROC) curves were used to assess the predictive performance of the FAR, determining the optimal predictive value.ResultsUltimately, 142 patients were included, with 71 in the HT group and 71 in the NHT group. After propensity score matching, a significant association was observed between the FAR and HT (OR = 1.40, 95% CI, 1.187–1.645; p <0.001). The ROC curve analysis indicated that the FAR predicted HT after intravenous thrombolysis, with an area under the curve (AUC) value of 0.751 (95% CI, 0.669–0.831; p <0.001) and an optimal cutoff value of 0.0918. The corresponding sensitivity and specificity were 78.9 and 60.9%, respectively.ConclusionIn ischemic stroke patients undergoing IVT, the FAR may serve as a promising biochemical marker for predicting HT following treatment.